2015
DOI: 10.3324/haematol.2015.128793
|View full text |Cite
|
Sign up to set email alerts
|

Renal complications in chronic lymphocytic leukemia and monoclonal B-cell lymphocytosis: the Mayo Clinic experience

Abstract: © F e r r a t a S t o r t i F o u n d a t i o ntent interstitial lymphocytic infiltration was observed. Standard processing of kidney biopsies evaluated at the Mayo Clinic included light microscopy, immunofluorescence, and electron microscopy. For light microscopy, biopsy specimens were stained with hematoxylin-eosin, periodic acid Schiff, Masson trichrome, and Jones methenamine silver. For immunofluorescence, 3-micron cryostat sections were stained with polyclonal fluorescein isothiocyanate-conjugated antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 42 publications
3
109
3
Order By: Relevance
“…chronic lymphocytic leukemia infiltration was the most common histopathologic finding, accounting for 73% of patients (70). The chronic lymphocytic leukemia infiltration often coexisted with other lesions, and granulomatous reaction was noted in some (62,71). Cryoglobulinemia GN (20%) was the most common glomerular lesion followed by minimal change disease (13.3%).…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…chronic lymphocytic leukemia infiltration was the most common histopathologic finding, accounting for 73% of patients (70). The chronic lymphocytic leukemia infiltration often coexisted with other lesions, and granulomatous reaction was noted in some (62,71). Cryoglobulinemia GN (20%) was the most common glomerular lesion followed by minimal change disease (13.3%).…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…A large study of 1043 patients newly diagnosed with chronic lymphocytic leukemia/small lymphocytic lymphoma found that 10% of patients had renal impairment, whereas another 14.5% developed renal impairment during the course of their disease (69). Another study from the same institution found that only 1.2% of all patients with chronic lymphocytic leukemia or MBL (n54024) underwent a kidney biopsy (62). Despite the lower prevalence, the variety of kidney diseases was similar to that of multiple myeloma and Waldenström macroglobulinemia.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 90% of pathology findings were either directly (infiltration) or indirectly (infection-associated) related to CLL, highlighting the apparent patho-biological relationship between CLL and renal function in some patients. 6 In the present cohort, RI was also acquired during the course of CLL follow up in an additional 151 patients. After adjusting for age and sex, factors associated with acquired RI during follow up included advanced Rai …”
Section: Letters To the Editormentioning
confidence: 99%
“…However, some recent evidence suggests that, in some cases, RI may be a consequence of CLL rather than simply reflecting an aging individual. 6 We aimed to investigate the specific prognostic role of renal function in the haematologica 2017; 102:e22 Patients had to have a baseline pre-treatment creatinine clearance available within one year prior to or three months after CLL diagnosis. Glomerular filtration rate was calculated using the Cockroft-Gault formula.…”
mentioning
confidence: 99%